Executive Dysfunction is Independently Associated with Reduced Functional Independence in Heart Failure - Alosco, Michael L. (J Clin Nurs, 2013)
AIMS AND OBJECTIVES: To examine the independent association between executive function with instrumental activities of daily living and health behaviors in older adults with heart failure. BACKGROUND: Executive function is an important contributor to functional independence as it consists of cognitive processes needed for decision-making, planning, organizing, and behavioral monitoring. Impairment in this domain is common in heart failure patients and associated with reduced performance of instrumental activities of daily living in many medical and neurological populations. However, the contribution of executive functions to functional independence and healthy lifestyle choices in heart failure patients has not been fully examined. DESIGN: Cross-sectional analyses. METHODS: 175 heart failure patients completed a neuropsychological battery and echocardiogram. Participants also completed the Lawton-Brody instrumental activities of daily living scale and reported current cigarette use. RESULTS: Hierarchical regressions revealed reduced executive function was independently associated with worse instrumental activity of daily living performance with a specific association for decreased ability to manage medications. Partial correlations showed executive dysfunction was associated with current cigarette use. CONCLUSIONS: Our findings suggest that executive dysfunction is associated with poorer functional independence and contributes to unhealthy behaviors in heart failure. Future studies should examine whether heart failure patients benefit from formal organization schemae (i.e., pill organizers) to maintain independence. RELEVANCE TO CLINICAL PRACTICE: Screening of executive function in heart failure patients may provide key insight into their ability to perform daily tasks, including management of treatment recommendations.